Cardinium endosymbionts are widespread in synanthropic mite species (Acari: Astigmata) - Kopecky, Jan; Perotti, M Alejandra; Nesvorna, Marta; Erban, Tomas; Hubert, Jan (Journal of invertebrate pathology, 2013)
'Candidatus Cardinium' is an intracellular endosymbiont or parasite frequently occurring in invertebrates including mites and ticks. In this work we report Cardinium bacteria in Astigmata mites and explore their incidence in synanthropic species. Amplification of a 776 bp bacterial 16S rRNA gene fragment, using specific primers, enabled identification of closely related Cardinium sequences in 13 laboratory-reared populations of mites. In addition, Cardinium sequences were identified in three wild mite populations. Large scale screening of these populations showed 100% prevalence of Cardinium, representing the highest incidence compared to other major Chelicerate groups.
Keywords: Phylogeny; Molecular Sequence Data; Animals; fylogeneze; Bacteroidetes; RNA ribozomální 16S; sekvenční analýza DNA; DNA, Bacterial; roztoči; Mites; Base Sequence; RNA, Ribosomal, 16S; zvířata; Sequence Analysis, DNA; sekvence nukleotidů; molekulární sekvence - údaje; Ascaris; DNA bakterií